2001
DOI: 10.1143/jjap.40.2540
|View full text |Cite
|
Sign up to set email alerts
|

Spot Scanning Using Radioactive11C Beams for Heavy-Ion Radiotherapy

Abstract: A scheme for spot scanning using 11C beams has been developed in order to form and verify a three-dimensionally conformal irradiation field for cancer radiotherapy. By selecting the momentum spread of a 11C beam, we could considerably decrease the distal falloff of the irradiation field, thus conserving the beam quality. To estimate and optimize the dose distribution in the irradiation field, it is essential to evaluate the precise dose distribution of spot beams. The coupling of the lateral dose and depth-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…In 2001, Urakabe et al . demonstrated that a positron-emitting 11 C scanned spot beam could be directly used as the therapeutic agent 29 . However, the estimate of RBE 10 used to obtain a flat biological dose was based on an extrapolation of previously-reported results for 12 C in water, which was assumed to extend to human tissue 30 .…”
Section: Related Workmentioning
confidence: 99%
“…In 2001, Urakabe et al . demonstrated that a positron-emitting 11 C scanned spot beam could be directly used as the therapeutic agent 29 . However, the estimate of RBE 10 used to obtain a flat biological dose was based on an extrapolation of previously-reported results for 12 C in water, which was assumed to extend to human tissue 30 .…”
Section: Related Workmentioning
confidence: 99%
“…The validity of the beam model and the optimization calculation had already been verified experimentally 15,16 by using the HIMAC spot scanning test course. 27 In the present simulation, we employed the measured dose response of the pencil beam with an energy of 350 MeV/ u, which corresponded to a 220 mm range in water. The beam size at the entrance and the width of the Gaussian-shaped mini peak was 3.5 and 4 mm at 1, respectively.…”
Section: Simulation Of Moving Target Irradiation With Rescanningmentioning
confidence: 99%
“…Although this method achieves production rates of almost 1%, which are deemed sufficient for testing purposes, the radioactive ion beams produced are considerably broad and feature larger momentum spreads than the projectile beam ( 36 , 38 ). Moreover, the production method is also characterized by the presence of impurities in the secondary beam, originating from the projectile fragments.…”
Section: Motivation For Carbon-11 Beams: Overview and Modelingmentioning
confidence: 99%